2016
DOI: 10.1038/nclimate2916
|View full text |Cite
|
Sign up to set email alerts
|

Increasing beef production could lower greenhouse gas emissions in Brazil if decoupled from deforestation

Abstract: Recent debate about agricultural greenhouse gases (GHG) emissions mitigation highlights tradeoffs inherent in the way we produce and consume food, with increasing scrutiny on emissionsintensive livestock products 1-3. While most research has focussed on mitigation through improved productivity 4,5 , systemic interactions resulting from reduced beef production at regional level are still unexplored. A detailed optimisation model of beef production encompassing pasture degradation and recovery processes, animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 21 publications
1
60
1
8
Order By: Relevance
“…Increasing beef production by 25% in Brazil would increase CH 4 emission by only 2.9% [53]. Recently, Oliveira Silva et al [51] reported reductions up to 10% of GHG emission by 2030 for a scenario of beef production intensification in Brazilian Cerrado to meet an increase of 30% of current beef consumption when decoupled from deforestation. Adoption of feedlot would be another feasible option to overcome dry periods of fodder scarcity when beef production is low but demand is high.…”
Section: Footprint Of Grain and Beefmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing beef production by 25% in Brazil would increase CH 4 emission by only 2.9% [53]. Recently, Oliveira Silva et al [51] reported reductions up to 10% of GHG emission by 2030 for a scenario of beef production intensification in Brazilian Cerrado to meet an increase of 30% of current beef consumption when decoupled from deforestation. Adoption of feedlot would be another feasible option to overcome dry periods of fodder scarcity when beef production is low but demand is high.…”
Section: Footprint Of Grain and Beefmentioning
confidence: 99%
“…The mean stocking of pastures in Brazil of 0.9 animal unit (AU) ha −1 [25] is too low and not sustainable. Therefore, increasing the stocking rate is a promising option for beef cattle production [51,52]. Beside genetic improvement to increase output, enhanced product quality and increased disease resistance of the livestock are among principal challenges.…”
Section: Footprint Of Grain and Beefmentioning
confidence: 99%
“…The message of those reports has not only damaged the reputation of animal production but in special the grassland based production systems in Latin America. This has triggered some reaction, and other research have challenged the mentioned reports (Glatzle et al, 2014;de Oliveira Silva et al, 2016). The global warming reports and other papers have stressed how the use of grain in the feed of ruminants can reduce enteric emission of GHG (Peters et al, 2010;Doreau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The sequestration of C by pasture plays an important role in partially mitigating the GHG emitted through ruminant production systems (Soussana et al, 2010;de Oliveira Silva et al, 2016). Carbon sequestration occurs principally as a result of the fixation of C via photosynthesis, which removes CO 2 from the atmosphere, and stores it as soil organic carbon (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…The intensification of the production system with the use of more efficient models of beef cattle production -through the ICL system, strategic nutritional supplementation, crossbreeding, and feedlot -makes it possible to increase productivity, by improving the use of areas and decreasing deforestation (Godfray et al, 2010;Silva et al, 2016). Crossbreeding between European and Zebu breeds is performed to improve the efficiency of meat production, as it increases the average daily gain in the post-weaning and shortens the production cycle.…”
Section: Introductionmentioning
confidence: 99%